To resist or not to resist? Investigating the normative features of resistance to persuasion. (18th March 2019) - Bonetto, Eric; Varet, Florent; Troïan, Jaïs
Abstract: Resistance to Persuasion (RP) is an important construct allowing to understand attitude change (or its absence) after persuasive attempts. Theorized as an individual attribute, no research has yet investigated the potential presence of prescriptive norms of judgment surrounding the display of RP by individuals. In line with the prevalence of individualistic values within occidental societies—where individuals are expected to be self‐determined, autonomous, self‐reliant, confident, and skillful—the present contribution therefore investigated whether displaying RP was subjected to social valorization. A first study, using a self‐presentation paradigm (within subjects, N = 106), showed that displaying RP conveyed a negative image of oneself. A second study, using a social judgment task (between subjects, N = 189), showed that targets displaying high RP were seen as less warm but more competent than targets displaying low RP. This effect was conceptually replicated in a third study using a different social judgment task (between subjects, N = 219). These results are interpreted in terms of social power and resistance to social influence. Practical implications are then discussed from two important perspectives: (a) the potential usefulness of power priming as a way to increase RP; (b) social norms surrounding RP as crucial moderators of intervention outcomes (e.g., focusing on critical thinking promotion). The existence of social valorization of not being resistant could be leveraged and could be crucial for applied psychologists, especially to optimize interventions aiming to fight against the spread of conspiracy theories and fake news among the public.